The Role of Muslim Family Motivation in Shaping Students' Interest in Entrepreneurship in Indonesia - Faqih Hanan Zaidan; Suci Rahmadani; Nayla Deshinta; Zultoni Lubis; Nur Alfiyah Nasywa (Adabiyah Islamic Journal, 2025)
This study was motivated by the limited interest in entrepreneurship among Indonesian students, while Muslim families have a strategic position as the initial environment for instilling Islamic values, attitudes, and work orientation. This study aims to describe the role of Muslim family motivation in shaping students' interest in entrepreneurship in Indonesia. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews and documentation of students from Muslim families, and is analyzed using thematic analysis techniques. The results show that Muslim family motivation plays an important role in fostering students' interest in entrepreneurship through emotional support, parental role modeling, moral encouragement, and the internalization of Islamic values such as hard work, independence, honesty, and the interpretation of entrepreneurship as part of worship and social responsibility. The conclusion of this study confirms that Muslim families function as the main agents in instilling an entrepreneurial orientation in students, so that strengthening the role of families based on Islamic values is an important strategy in fostering an entrepreneurial spirit among the younger generation and supporting sustainable economic development in Indonesia.